1990
DOI: 10.1073/pnas.87.17.6547
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus infection is associated with the development of hepatocellular carcinoma.

Abstract: A possible causative role for the recently discovered hepatitis C virus (HCV) in the development of hepatocellular carcinoma (HCC) was investigated by assay of sera from HCC patients in Japan for antibodies to a recombinant HCV antigen and to hepatitis B virus (HBV) antigens. Among the 253 HCC patients examined, 156 (61.7%) had no serum markers of either a previous or a current HBV infection (group I), 46 (18.2%) were negative for HBV surface antigen but positive for anti-HBV surface and/or anti-HBV core antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
643
0
4

Year Published

1991
1991
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,048 publications
(651 citation statements)
references
References 17 publications
4
643
0
4
Order By: Relevance
“…Blood screening based on the cloned HCV genome and its gene products has reduced significantly the blood-borne HCV transmission [1][2][3]. However, detailed studies of HCV (for example, virus replication, pathogenicity, and natural history of HCV) have been greatly hampered by the lack of efficient in vitro culture systems of HCV infection.…”
Section: Introductionmentioning
confidence: 99%
“…Blood screening based on the cloned HCV genome and its gene products has reduced significantly the blood-borne HCV transmission [1][2][3]. However, detailed studies of HCV (for example, virus replication, pathogenicity, and natural history of HCV) have been greatly hampered by the lack of efficient in vitro culture systems of HCV infection.…”
Section: Introductionmentioning
confidence: 99%
“…Infection by hepatitis C virus (HCV), the main causative agent of posttransfusion hepatitis, frequently leads to liver cirrhosis and hepatocellular carcinoma (Saito et al+, 1990)+ An estimated 170 million people are infected by the virus, of whom 10-20% are expected to suffer these life-threatening complications (Cohen, 1999)+ The viral proteins are translated from a 9+5-kb single-stranded positive sense RNA, which is flanked by 59 and 39 untranslated regions (UTRs) (Houghton et al+, 1994)+ The 59 UTR represents the most conserved region of the genome (Bukh et al+, 1992)+ It forms the highly structured internal ribosome entry site (IRES) (nt 40-370), which directs translation in a cap-independent manner (Reynolds et al+, 1996), a mechanism first observed in picornaviruses (Jackson et al+, 1990)+…”
Section: Introductionmentioning
confidence: 99%
“…Evaluation of the risk factors for HCC in CLD patients is imperative. Identification of the individuals who are at higher risk of HCC would contribute to the early diagnosis of this disease and to effective implementation of strategies for chemoprevention.Numerous epidemiological and biological studies have indicated that a chronic infection with hepatitis B virus (HBV) and/or hepatitis C virus (HCV) plays an important role in hepatocarcinogenesis (Bruix et al, 1989;Saito et al, 1990;Kim et al, 1991). As for HBV, serum hepatitis B surface antigen (HBsAg) positivity, which indicates a chronic HBV carrier state, is a well-established risk factor for HCC (Beasley et al, 1981;Chen et al, 1991).…”
mentioning
confidence: 99%